2022
DOI: 10.1038/s41598-022-22052-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of yam varieties on flour physicochemical characteristics and resultant instant fufu pasting and sensory attributes

Abstract: Challenges and constraints deter the effective gathering of adequate information specific to the characteristics of yam (Dioscorea rotundata) landraces capable of producing a promising instant pounded fufu product. This current work, therefore, investigated the effects of yam varieties on flour physicochemical characteristics and resultant instant fufu pasting and sensory attributes. The D. rotundata varieties, obtained from the International Institute of Tropical Agriculture (IITA) (yam-breeding programme) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(31 reference statements)
1
4
0
Order By: Relevance
“…NPK fertiliser application did not significantly affect the swelling power and solubility index of yam flour. The values of the functional and pasting properties of yam flours made from tubers grown with and without fertilisation were comparable to those reported in previous studies [7][8][9][10][11]. Ebúrneo et al [19] reported that nitrogen fertilisation affects starch grain size, shape, and pasting temperature in potatoes, while Gunaratne et al [35] showed that fertilisation increased the protein content but decreased the amylose content of rice flour, which affected its functional and pasting properties.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…NPK fertiliser application did not significantly affect the swelling power and solubility index of yam flour. The values of the functional and pasting properties of yam flours made from tubers grown with and without fertilisation were comparable to those reported in previous studies [7][8][9][10][11]. Ebúrneo et al [19] reported that nitrogen fertilisation affects starch grain size, shape, and pasting temperature in potatoes, while Gunaratne et al [35] showed that fertilisation increased the protein content but decreased the amylose content of rice flour, which affected its functional and pasting properties.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to pounded yam, dried yam tubers are processed into flour which is used in preparation of an important staple food in West Africa. The functional and pasting properties of Dioscorea alata and Dioscorea rotundata flours influence the quality of pounded yams, and interspecific differences in these landraces have been reported [7][8][9][10][11]. Baah et al [9] observed that the trough viscosity of flour is Agriculture 2023, 13, 2240 2 of 14 associated with the consistency and elasticity of pounded yams, and the final viscosity is most commonly used to evaluate the quality of flour samples because it reflects the capacity for forming viscous pastes after cooking and cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Amala and pounded yam are two major traditional cuisines from yam tubers in Nigeria. Particularly, the pounded yam holds a major position, with consumption spanning many ethnic groups (Ufondu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Using this crop's industrial potential will allow it to transit out of its current subsistence state and encourage the formation of small businesses, which will boost economic growth (Otegbayo et al, 2014). The farmers, consumers, and various yam end users are further guided on the utilization of yam food products by the tuber's physicochemical, functional, and sensory qualities (Ufondu et al, 2022). The objective of this study is to investigate the physicochemical and sensory properties of five varieties of white yam in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to enhance the cooking quality of yam, particularly hardness and moldability, in breeding programs involve genetic studies [25][26][27][28]. Dioscorea alata is renowned for its favorable agronomic performance and widespread cultivation.…”
Section: Introductionmentioning
confidence: 99%